MICRO, SMALL, AND MEDIUM ENTERPRISES ON ONLINE MEDIA - E S Soegoto; M A Rahman; T P Sumitra (LP2M Universitas Bina Bangsa, 2022)
The objective of this study is to analyze the impact of the product promotion method of Micro, Small, and Medium Enterprises (MSME) on selling products based on online media. This study used a descriptive qualitative method. The result of this study is to find out the effective and efficient product promotion in product sales, also to produce quality human resources to develop Indonesia in the field of commerce based on online media. The focus includes Entrepreneurship, Economics, Communication, and Information Technology. MSME based on online media has become a medium that provides business opportunities; therefore, the goal of increasing Indonesia's economy can be achieved